2017
DOI: 10.1177/0004867417713664
|View full text |Cite
|
Sign up to set email alerts
|

Sexual minority youth and depressive symptoms or depressive disorder: A systematic review and meta-analysis of population-based studies

Abstract: Objective: Research has suggested that sexual minority young people are more likely to have depressive symptoms or depressive disorder, but to date most studies in the field have relied on convenience-based samples. This study overcomes this limitation by systematically reviewing the literature from population-based studies and conducting a meta-analysis to identify whether depressive disorder and depressive symptoms are elevated in sexual minority youth. Method:A systematic review and meta-analysis were condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
169
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 213 publications
(201 citation statements)
references
References 66 publications
(82 reference statements)
11
169
2
3
Order By: Relevance
“…Sexual minorities (for example people identifying as lesbian, gay or bisexual, not exclusively heterosexual or not sure of their sexual orientation 1,2 ) are more likely to experience depression, self-harm and suicide attempts than heterosexuals. 2,3 These associations have been reported in cross-sectional surveys across the world, in adults 2,3 and adolescents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sexual minorities (for example people identifying as lesbian, gay or bisexual, not exclusively heterosexual or not sure of their sexual orientation 1,2 ) are more likely to experience depression, self-harm and suicide attempts than heterosexuals. 2,3 These associations have been reported in cross-sectional surveys across the world, in adults 2,3 and adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 These associations have been reported in cross-sectional surveys across the world, in adults 2,3 and adolescents. 4,5 However, there is little longitudinal research on when increased risk for these mental health problems emerges and how it develops over time.…”
Section: Introductionmentioning
confidence: 99%
“…A wealth of research has demonstrated mental health disparities among SMY relative to their heterosexual counterparts (Lucassen et al., ) and that SMY report greater unmet health care needs (Ramos et al., ). The current study aimed to examine whether sexual orientation–based differences in mental health indicators were smaller in schools with SBHCs than those without SBHCs among a representative sample of Oregon adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Research examining sexual and reproductive health have shown that SBHCs activities support adolescents’ self‐efficacy toward health practices (Mesheriakova & Tebb, ; Weeks et al., ). Alternatively, it may be that SBHC presence may be especially impactful for SMY given increased need based on disproportionate rates of mental health problems (Lucassen et al., ). Indeed, the current study did not find that SBHC presence was associated with non‐SMY mental health indicators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation